Propuesta metodológica para la toma de decisión entre comprar o alquilar maquinarias agrícolas - Orellana Pardavé, José Antonio (2022)
This publication compared the costs of agricultural operations of plowing, tracking, planting and fumigation that involve the acquisition of new equipment versus the cost of leasing the services of attending the same tasks to third parties. For this, a methodology was developed based on the calculation of fixed and variable costs, considering the amortization and interest costs as fixed and the consumption of fuel, lubricants, maintenance costs and wages as variable. It was obtained as a result, for a family business dedicated to the production of hard yellow corn with three fields of 22, 25 and 32 hectares in the San Martín region, that the option of investing in new equipment is not feasible in terms of costs, concluding Finally, the best option is to hire the services of the companies specialized in leasing in the surrounding areas for the 2019-2020 campaign. Keywords: Costs; farm machinery; rent; to lease; to buy; decision.